Transcriptomic analysis of bovine endometrial epithelial cells in response to interferon tau and hormone stimulation - Yu, Jie; Liu, Chenhui; Chen, Hongbo; Xiang, Min; Hu, Xiuzhong; Zhong, Zhuxia; Liu, Qing; Wang, Dingfa; Cheng, Lei (Frontiers in Veterinary Science, 2024)
The embryonic loss during early stage of gestation is one of the major causes of infertility for domestic ruminants, causing huge economic losses to pasture.Maternal recognition of pregnancy and implantation are the crucial process for determining the successful establishment and development of pregnancy in cattle. The research on molecular mechanisms of pregnancy recognition will facilitate illustrating the complex process of pregnancy establishment and help to improve pregnancy outcomes. In this study, we performed transcriptomic analysis of primary bovine endometrial epithelial cells (BEND) with or without IFNT and hormones intervention through RNA sequencing. We eventually identified 608 differentially expressed genes (DEGs) including 409 up-regulated genes and 199 down-regulated genes in IFNT and hormones-treated group compared with control group. Gene Ontology (GO) enrichment analysis demonstrated that the majority of DEGs were implicated in immune system process, response to external stimulus, response to cytokine, regulation of response to stress. Results from KEGG analysis showed a significant enrichment of NOD-like receptor signaling pathway, antigen processing and presentation, necroptosis, oxidative phosphorylation, RIG-I-like receptor signaling pathway. Additionally, a set of promising candidate genes, including (USP18, STAT1, PSMB8, IFIH1, MX2, IFI44, DHX58, CASP8, DRAM1, CXCR4), were characterized by constructing an integrated interaction network. Specifically, the mRNA expression of HOXA11, PTGS1 and PTGS2 were remarkably suppressed by silencing DRAM1 under IFNT and hormone administration, thus speculating that DRAM1 might play a crucial role in early pregnancy by regulating endometrial function. The results of this study depicted a relatively comprehensive transcriptional profiles of BEND in response to IFNT and hormones, which contributes to a better understanding of gene interaction network and underlying regulatory mechanisms in endometrium of ruminants during early pregnancy.